Bringing Climate Into the Classroom: Inside a Teaching Retreat Around Naomi Klein’s This Changes Everything - Bigelow, Bill; Kelly, Alex; McKenna, Katie (Radical Teacher, 2015)
Jill Howdyshell lives and teaches 5th grade in Togiak, a small Yu’pik fishing village in southwestern Alaska. In Togiak, harvesting berries is a practice that goes back countless generations. The berries are the key ingredient in akutaq, called eskimo ice cream. In her classes, Howdyshell’s students write identity poems with lines proclaiming “I am from akutaq,” and describing cherished excursions with parents and grandparents. In 2014, residents discovered that there would be no berries that year: the tundra had not frozen for a sufficient length of time for the berries to regenerate. With a dramatic rise in temperatures, Yu’pik people can no longer rely on digging deep into the permafrost to store food in makeshift freezers. And most distressing: as a result of rising seas, during the next few years, Yu’pik people will be forced to relocate large parts of their community.